CHILDHOOD VACCINATION: MEDICAL BENEFITS, PUBLIC HEALTH IMPACT, AND PARENTAL RESPONSIBILITIES - Asatullyev Rustam,; Xudoynazarova Xadisa, (TADQIQOTLAR, 2026)
Abstract: Childhood vaccination represents one of the most successful public health interventions in modern medical history. This article provides a comprehensive analysis of childhood vaccination, examining its medical efficacy, safety profile, public health  impact,  current  global  coverage  trends,  and  the  complex  legal  and  ethical considerations  surrounding  parental  decision-making.  Drawing  on  recent  Cochrane reviews,  WHO  and  UNICEF  data,  and  contemporary  legal  scholarship,  this  article demonstrates  that  vaccines  have  prevented  hundreds  of  millions  of  illnesses  and millions  of  hospitalizations  over  the  past  three  decades.  However,  declining vaccination  rates  in  several  countries  threaten  herd  immunity  and  have  led  to  the resurgence of previously controlled diseases such as measles. The article also explores the legal framework governing childhood vaccination, particularly the tension between parental  autonomy  and  children's  rights  to  health  protection.  The  evidence overwhelmingly  supports  vaccination  as  a  safe,  effective,  and  cost-effective intervention that benefits not only individual children but entire communities.